Cell therapy for medication-related osteonecrosis of the jaw: update on treatment strategies - N Kaibuchi; T Iwata; T Okamoto; Y Kawase-Koga; M Yamato (European Cells & Materials, 2021)
Despite extensive research since the first report of medication-related osteonecrosis of the jaw (MRONJ) in 2003, the optimal treatment and preventive modalities for the condition are not clear. Therefore, its management has been a concern in dentistry, oral and maxillofacial surgery, as well as departments involved in the treatment of cancers and/or bone diseases worldwide. Several cases of MRONJ could not be cured by conventional treatment strategies, as per the recommendations in various position papers. Therefore, a number of studies, including randomized controlled trials, have been conducted to examine the efficacy of novel therapies. However, no definite treatment modality has been determined. Several types of cell therapies have been documented. 10 animal studies and 5 case reports have been documented, in which autologous transplantation of cells has been carried out in MRONJ patients. Although these reports showed the efficacy of cell therapy, they were not large-scale, statistically accurate clinical studies; hence, the efficacy of cell therapy for this condition is not certain. However, the efficacy of MRONJ treatment using mesenchymal stromal cell (MSC) sheets has been investigated since 2013. This has been confirmed through various experiments in which MSC sheets were transplanted into model rats and beagle dogs exhibiting MRONJ-like lesions. Based on these results, a clinical study of MRONJ treatment using periodontal ligament-derived MSC sheets is being currently planned.